The impact of earthworms on collembolan (Collembola) communities in grass mono- and polycultures - Olejniczak, Izabella; Makulec, Grzegorz (Studia Ecologiae et Bioethicae, 2020)
In 2004-2005, a lysimetric experiment was designed to determine whether and how plant diversity and earthworms could influence diversity and densities of collembolan communities. We compared two types of crops: monoculture of Festuca rubra L. and a polyculture, the mixture of grasses (8 species) commonly used in agriculture. In addition to two plant communities of different diversity, we used in our experiments an engineering species of earthworm – Aporrectodea caliginosa (Sav.). The experiment was initiated in May 2004, when the lysimeters were sown with F. rubra or with a mixture of grasses. The following year, in May 2005, we introduced 6 individuals (that correspond with average densities of 200 ind. m-2 in the natural environment) of A. caliginosa to half of the lysimeters. Soil samples were taken at the depths of 0-5 cm, 5-10 cm, 10-15 cm and 15-20 cm, before introducing earthworms and after 60, 120 and 180 days from introducing earthworms. We found that soil layer (Kruskal-Wallis test: N=432, H=18.25, P=0.0004), biodiversity of grass culture (N=432, H=14.59, P=0.0001) and the period of the season (N=432, H=24.24, P=0.0000) had an important effect on densities of collembolan communities independently of earthworms presence (N=432, H=1.99, P=0.16). We found 18 species of springtails and the number of species decreased with soil layer. The most abundant were Proisotomodes bipunctatus and Isotomodes productus.